Potret Kinerja Fiskal Kabupaten/Kota Di Indonesia Sebelum dan Setelah Pelaksanaan Otda - Nanga, Muana (Jurnal Ilmiah Ranggagading (JIR), 2005)
Regions now posses authority to make policies for services, participation increase, initiatives, and people empowerment whose purpose is to increase the prosperity of the people. In line with the principles another principle is also applied â real and responsible autonomy, that is the principle in which the governmental issues management is conducted based on the tasks, authority, and obligation which obviously has existed and had the potentials to grow, live and develop in accordance with the potentials and specialty of the region. Hence, the implementation of regional autonomy must always be oriented to the enhancement of the peopleâs prosperity by always paying attention to the interest and aspiration existing in the community. Key words: Regional Autonomy; Fiscal Performance.